Frames de los latinoamericanos inmigrantes en España y su relación con los estereotipos - Rotavista Pinzón, Martha Karina (2025)
A five-year content analysis of 300 news articles from the newspapers El País and El Mundo examines how Latin Americans are positioned within media narratives. Additionally, through a focus group, these frames are compared with the perceptions held by some Spanish citizens. According to the National Statistics Institute (INE), there are 1,554,900 Latin Americanslegally residing in Spain, primarily from Colombia, Ecuador, Bolivia, and Venezuela. Although newspapers such as El País and El Mundo acknowledge their presence, there remains a notable lack of information, representation, and in-depth coverage regarding this immigrant population.